2020
DOI: 10.1371/journal.pone.0233839
|View full text |Cite
|
Sign up to set email alerts
|

Barriers & facilitators to healthcare and social services among undocumented Latino(a)/Latinx immigrant clients: Perspectives from frontline service providers in Southeast Michigan

Abstract: Immigration-and enforcement-related policies and laws have significantly and negatively impacted the health and well-being of undocumented immigrants. We examine barriers and facilitators to healthcare and social services among undocumented Latino(a)/Latinx immigrants specifically in the post 2016 US presidential election socio-political climate. By grounding our study on the perspectives of frontline providers, we explore their challenges in meeting the needs of their undocumented clients. These include clien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 29 publications
1
45
0
Order By: Relevance
“…The research question addressed in this manuscript was identified later in the process after our committee analyzed and disseminated initial results (Doshi et al, 2020; Fleming et al, 2019; Mesa et al, 2020). After these initial findings, partner agencies and clients wanted to focus on how to respond to mental health concerns within these communities.…”
Section: Methodsmentioning
confidence: 99%
“…The research question addressed in this manuscript was identified later in the process after our committee analyzed and disseminated initial results (Doshi et al, 2020; Fleming et al, 2019; Mesa et al, 2020). After these initial findings, partner agencies and clients wanted to focus on how to respond to mental health concerns within these communities.…”
Section: Methodsmentioning
confidence: 99%
“… 3 These challenges are manifested in concrete process measures, such as delays in the decision to seek care, difficulty in identifying and traveling to health care facilities, and receipt of lower quality care at those facilities. 8 …”
Section: Introductionmentioning
confidence: 99%
“…Lack of insurance and other policy restrictions create an environment of fear and stress that dissuade patients from seeking care, even when absolutely necessary. 8 , 13–16 The recent promulgation of the public charge rule, a federal regulation that limits the social services immigrants can utilize to qualify for legal permanent residency, has exacerbated this sense of fear and avoidance of the health care system. 2 , 17 In addition to the policies that directly restrict health care access, several federal and local measures curtail social and economic opportunities for PWDS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Black or Latino/a adults also had increased access to healthcare, but they still face less access than White adults. It is at least noteworthy that there was no significant improvement among the Latino population, which could be associated with language barriers, limited experience using health insurance, and eligibility requirements which have been documented elsewhere (Doshi et al., 2020; Edward et al., 2018). Our findings suggest that earlier research on the challenges that rural residents face accessing healthcare might apply more to low‐income, nonwhite groups as opposed to rural residents overall.…”
Section: Discussionmentioning
confidence: 80%